Contested belonging : spaces, practices, biographies - Davis, Kathy, 1949-; Ghorashi, Halleh; Smets, Peer (Emerald Publishing Limited, 2018)
In 'Contested Belonging: Spaces, Practices, Biographies' contributions by well-known international scholars from different disciplines address the sites, practices, and narratives in which belonging is imagined, enacted and constrained, negotiated and contested. Belonging is viewed from the perspectives of both migrants and refugees in their host countries as well as from people who are ostensibly at home and yet may experience various degrees of alienation in their countries of origin. The book focuses on three particular dimensions of belonging: belonging as space (neighbourhood, workplace, home), as practice (virtual, physical, cultural), and as biography (life stories, group narratives). What role do physical, digital, transnational and in-between spaces play and how are they used in order to create/contest belonging? Which practices do people engage in in order to gain/foster/invent a certain/new sense of belonging? What can the biographies and narratives of people reveal about their complicated and contested experiences of belonging? Contested Belonging: Spaces, Practices, Biographies convincingly shows how individual and collective struggles for belonging are not only associated with exclusion and othering, but also lead to surprising and inspiring forms of social action and transformation, suggesting that there may be more reason for hope than for despair.